IMPLEMENTASI STRATEGI RE-BRANDING VISUAL TERHADAP KAMPUNG TEMATIK JAHIT “KABAYA” KELURAHAN RANGKAH - Nabilah, Firyal; Muhammad Bhirawa Dwi Atma Citalada; Lutfi Hamidah; Vanza Satria Pringga Pratama; Mohammad Naufal Adityo; Kevin Ricky Pradana; Sherly Lawalata (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
The Sewing Thematic Village in Rangkah Subdistrict faces challenges in market expansion due to the absence of a strong visual identity. Visual identity plays a crucial role in branding strategy and building brand awareness. This Community Service Program aims to assist the residents of the Sewing Thematic Village in designing and strengthening their visual identity and increasing public brand awareness. The method involved participatory discussions, logo and visual design, village profile video production, visual media installations, and the inauguration of the village’s name and logo. The results show increased awareness among residents regarding branding importance and the enhancement of brand assets through installed visuals in active tailor houses. This activity also helps establish the village’s image as a creative hub for sewing-based businesses. The outcomes are significant as a foundation for sustainable marketing strategies for local SMEs and demonstrate how community-based branding can enhance the competitiveness of thematic villages.